Nationalisation of local party systems in Belgium (1976-2018): the combined effects of municipality size and parliamentary parties' dominance. Issue 1 (2nd January 2021) - Dodeigne, Jeremy; Close, Caroline; Teuber, Ferdinand
ABSTRACT: This article studies the nationalisation of local party systems in Belgian regions across eight electoral cycles (1976–2018). Our research design assesses the relevance of Rokkan's structural approach of nationalisation while testing the effect of conjunctural electoral factors. Our empirical results highlight the positive effect of a municipality's size on local party system nationalisation. Moreover, the analysis uncovers the impact of the electoral dominance of national parties in the local districts at previous national elections: where parliamentary parties have performed weakly at the previous national elections, nationalisation of local party systems increases.Interestingly, the analysis demonstrates that this relationship is stronger in the biggest municipalities, showing an interaction effect between conjunctural and structural factors. Finally, our findings indicate that significant variation remains across Belgian regions . This opens up avenues for future research regarding the potential effects of institutional factors and the 'freezing' of local political offer across subnational party systems.